PEMBERDAYAAN PELAKU UMKM MELALUI PROGRAM SOSIALISASI STRATEGI PEMASARAN UNTUK MENINGKATKAN DAYA SAING PRODUK LOKAL DI DESA KELORAN - S Sugiyat; Annafi' Nurul 'Ilmi Azizah; Arif Effendi; Aflahul Mu’min; Mustajabah Khoirun Nisa' Muna Afifah; Mario Wijaya Putra; Zulfa Nida Khoiriyah (AL HAZIQ: Journal of Community Service, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in strengthening the local economy; however, limited marketing knowledge and skills remain a major challenge for rural business actors. This community service program aimed to enhance the marketing knowledge and skills of MSME actors in Keloran Village through a marketing strategy socialization program. The activity was conducted on January 28, 2026, at the Keloran Village Office, Wonogiri, involving 40 participants consisting of MSME actors and members of the Family Welfare Empowerment (PKK) group. The program applied a participatory approach through lectures, interactive discussions, question-and-answer sessions, and direct product promotion and sales practices. The materials covered marketing strategies, product packaging and branding, as well as the utilization of marketing media to improve product competitiveness. The results indicated an increase in participants’ understanding of effective marketing strategies, greater awareness of the importance of business legality, and active engagement throughout the program. As a follow-up action, assistance was provided for MSME actors who had not yet obtained a Business Identification Number (NIB) to support business formalization and sustainability.